Online Support Group Participation and Social Support: Incorporating Identification and Interpersonal Bonds. (October 2019) - Zhu, Yaguang; Stephens, Keri K.
An increasing number of people with chronic diseases exchange social support using online support groups (OSGs). However, there is little understanding of group communication mechanisms that underpin the relationship between OSG participation and social support. Drawing on Prentice, Miller, and Lightdale's common-identity and common-bond framework, we propose and test a theoretical model that explains group communication mechanisms through which members' participation influences their perceived social support. In the process, we identified and empirically validated a three-factor solution for an OSG participation scale. Based on 356 users across 12 popular OSGs, we find that two group communication mechanisms—identification with the community and interpersonal bonds with other members—mediate the relationship between OSG participation and perceived social support. Specifically, identification has a stronger mediating effect than interpersonal bonds in the relationship between OSG participation and perceived social support. We also discuss theoretical and practical implications.